Optimalisasi Strategi Pembelajaran Islami dalam Menumbuhkan Kecerdasan Spiritual Peserta Didik - Mutia Ananda; Fauza Rahmadani; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic education plays a crucial role in shaping the character and spiritual intelligence of students. Through Islamic learning strategies, students are not only provided with religious knowledge but also guided to develop moral, ethical, and spiritual values in their lives. This article discusses the influence of Islamic education on the development of spiritual intelligence, the role of educators, and the challenges and implications of its implementation. The research findings show that Islamic education significantly contributes to the formation of disciplined, honest, responsible, and empathetic individuals. Although there are some challenges in the implementation of this strategy, such as limited resources and resistance to religion-based approaches, Islamic learning strategies can have a significant positive impact on the moral and spiritual development of students. Islamic education also has positive implications in students' social relationships and the development of environmental awareness.